Double Beta Decay Experiments: Recent Achievements and Future Prospects - Alexander Barabash (Universe, 2023)
The results of experiments on the search for and study of double beta decay processes obtained over the past 5 years (from 2018 to April 2023) are discussed. The results of the search for neutrinoless double beta decay are presented, in which a sensitivity of <semantics>T1/2∼2×1024</semantics>–<semantics>2×1026</semantics> years (90% C.L.) has been achieved. The present conservative upper limit on effective Majorana neutrino mass <semantics>⟨mν⟩</semantics> was established from these experiments as 0.16 eV (90% C.L.). The results of experiments on recording and studying the processes of two-neutrino double beta decay in various nuclei (transitions to both the ground and excited states of daughter nuclei) are discussed too. The results of experiments on the search for majoron are also given. Possible progress in this field in the future is discussed.